2014
DOI: 10.1038/bjc.2014.279
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the tumour stroma percentage, clinicopathological characteristics and outcome in patients with operable ductal breast cancer

Abstract: Background:The percentage of tumour stroma (TSP) has recently been reported to be a novel independent predictor of outcome in patients with a variety of common solid organ tumours. The aim of this study was to examine the relationship between TSP, clinicopathological characteristics and outcome in patients with invasive ductal breast cancer, in particular node negative and triple negative disease.Methods:A total of 361 patients with primary operable invasive ductal breast cancer were included in this study. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 30 publications
11
92
1
1
Order By: Relevance
“…The prognostic significance of tumour stroma has been reported in breast cancer 13–16. Gujam et al 16 also showed a correlation between a high percentage (>50%) of tumour stroma and low-grade tumour inflammatory infiltration. However, those authors only evaluated the relationship between tumour stroma and peritumoral lymphocytic infiltration without evaluation of TILs in the interior of invasive tumours.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The prognostic significance of tumour stroma has been reported in breast cancer 13–16. Gujam et al 16 also showed a correlation between a high percentage (>50%) of tumour stroma and low-grade tumour inflammatory infiltration. However, those authors only evaluated the relationship between tumour stroma and peritumoral lymphocytic infiltration without evaluation of TILs in the interior of invasive tumours.…”
Section: Introductionmentioning
confidence: 90%
“…Slides were histopathologically analysed for (i) TILs (defined as the mean percentage of stroma of invasive carcinoma infiltrated by lymphocytes and plasma cells in 10% increments; if <10% of stroma was infiltrated by TILs, 1% or 5% criteria were used; all available full sections were evaluated);1 19 (ii) the amount of inflammatory cells evaluated at the tumour's invasive margin (according to Klintrup criteria; score 0, no inflammatory cells at the invasive margin; score 1, mild and patchy increase of inflammatory cells; score 2, increased inflammatory cells forming a band-like infiltration at the invasive margin; score 3, prominent inflammatory reaction forming a cup-like zone at the invasive margin);6 20 (iii) aggregation of lymphoid cells in terminal duct lobular units (TDLUs; within 5 mm and >5 mm from the invasive or in situ carcinoma); (iv) the amount of TLSs in adjacent tissue including the in situ component (none, no TLS formation in the area adjacent to the tumour; little, TLSs occupying an area of <10% of the circumference of the tumour; moderate, 10–50%; or abundant, >50%; shown in figure 1); (v) the presence or absence of a germinal centre in TLSs; (vi) the percentage of tumour stroma in the most invasive tumour area (high percentage of tumour stroma, >50%; low percentage of tumour stroma, ≤50%);16 (vii) heterogeneity of the tumour (heterogeneous: invasive tumour mixed with normal breast parenchyma; homogeneous: invasive tumour mass without normal breast parenchyma); (viii) histological subtype and grade, percentage of in situ component, tumour size, pT stage, pN stage and lymphovascular invasion. Lymphoid aggregation with vessels showing HEV features (plump, cuboidal endothelial cells) with or without germinal centres was considered a TLS.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…In recent research, some new parameters have emerged that may have a prognostic role in colorectal cancer, one of them being the amount of stroma, which was fi rst demonstrated as a prognostic factor in breast and esophageal cancer [17][18][19][20][21][22] . Th e role of stroma proportion, or tumor cell proportion in the prognosis of colorectal cancer has been reported in four papers so far; they have demonstrated the proportion of stroma to be a signifi cant prognostic factor in colorectal cancer and the higher proportion of tumor stroma to be associated with better patient prognosis 24,25,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that stroma induces tumorigenesis by various mechanisms such as remodeling of extracellular matrix, suppression of immune response and motility, as well as aggressiveness of cancer cells [15][16][17] . It has been evident that stroma has a prognostic value in esophageal cancer 18,19 and breast cancer 20 , especially triple negative breast cancer 21,22 . Using simple modifi ed methodology, we tried to determine the impact of stroma proportion on progression-free survival and overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Un même ordre de fréquence est rapporté dans le carcinome canalaire invasif du sein chez la femme (moyenne pondérée de 33% en HES avec un intervalle allant de 10 à 49%) selon la méta-analyse de Gujam et al (2014b).…”
Section: Fréquence De L'embolisation Lymphatiqueunclassified